Large trilobites in a stress-free Early Ordovician environment. (18th February 2021) - Saleh, Farid; Vidal, Muriel; Laibl, Lukáš; Sansjofre, Pierre; Gueriau, Pierre; Pérez-Peris, Francesc; Lustri, Lorenzo; Lucas, Victoire; Lefebvre, Bertrand; Pittet, Bernard; El Hariri, Khadija; Daley, Allison C.
Abstract: Understanding variations in body size is essential for deciphering the response of an organism to its surrounding environmental conditions and its ecological adaptations. In modern environments, large marine animals are mostly found in cold waters. However, numerous parameters can influence body-size variations other than temperatures, such as oxygenation, nutrient availability, predation or physical disturbances by storms. Here, we investigate trilobite size variations in the Lower Ordovician Fezouata Shale deposited in a cold-water environment. Trilobite assemblages dominated by small- to normal-sized specimens that are a few centimetres in length are found in proximal and intermediate settings, while those comprising larger taxa more than 20 cm in length are found in the most distal environment of the Fezouata Shale. Drill core material from distal settings shows that sedimentary rocks hosting large trilobites preserved in situ are extensively bioturbated with a high diversity of trace fossils, indicating that oxygen and nutrients were available in this environment. In intermediate and shallow settings, bioturbation is less extensive and shallower in depth. The rarity of storm events (minimal physical disturbance) and the lack of predators in deep environments in comparison to shallower settings would also have helped trilobites attain larger body sizes. This highly resolved spatial study investigating the effects of numerous biotic and abiotic parameters on body size has wider implications for the understanding of size fluctuations over geological time.